Therapeutic Management of Hypothyroidism in Dogs - Nagella Naveen; N. Lakshmi Rani; K. Basava Reddy; V. Devi Prasad (The Indian Veterinary Journal, 2025)
The present study was conducted at Veterinary Clinical Complex of NTR College of Veterinary Science, Gannavaram, from March to November 2023,found a hospital prevalence of hypothyroidism at 0.45% (27/5957).Ten hypothyroid dogs (Group II) treated with Levothyroxine (0.02 mg/kg daily) had significantly (p